1989
DOI: 10.1103/physrevb.40.1064
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of ion-implanted GaAs: The observation of finite-size effects in GaAs microcrystals

Abstract: We have carried out reflectivity measurements, for photon energies from 2.0 to 5.6 eV in the electronic interband regime, for a series of unannealed ion-implanted GaAs samples which had been exposed to 45-keV We propose a simple theory of the finite-size effects which, when combined with band-structure information for GaAs, semiquantitatively accounts for our observations. Small microcrystal size implies a short time for an excited carrier to reach, and be scattered by, the microcrystal boundary, thus limiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…E 0 is the peak transition energy that corresponds to the so-called Penn gap. Γ is the broadening parameter, inversely related to short-range order [17] and crystallite size [18].…”
Section: 1-backgroundmentioning
confidence: 99%
“…E 0 is the peak transition energy that corresponds to the so-called Penn gap. Γ is the broadening parameter, inversely related to short-range order [17] and crystallite size [18].…”
Section: 1-backgroundmentioning
confidence: 99%
“…The nanocrystal formation was also observed by Campomanes et al [1] in non-hydrogenated GaAs samples prepared by flash evaporation after thermal treatment at 600 C for two hours. Feng and Zallen [9] also have produced a nanocrystalline GaAs structure. In this case the structure was attained by Be + ion bombardment of a crystalline GaAs surface.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies also have shown that is possible to produce nanocrystalline GaAs, using processes that involve [8] or not [9] hydrogen incorporation. The new properties of the nanostructured GaAs open new possibilities of technological applications for this widely used electronic material.…”
Section: Introductionmentioning
confidence: 99%
“…A general empirical approach is to use a combination of Lorentz oscillators. This method allows the determination of the critical point energies and the layer thickness [13].…”
Section: Measurable Nanocrystal Propertiesmentioning
confidence: 99%
“…F. Feng and R. Zallen [13] used Raman spectroscopy to verify the linearity between broadening and reciprocal grain size (Fig. 6) Whether one needs an additional transition layer to achieve a good fit Surface nanoroughness As a homogeneous roughness layer or using more sophisticated methods Shape of crystals…”
Section: Applicationsmentioning
confidence: 99%